Complexité et Log-périodicité des remontées mécaniques pour skieurs - Ivan Brissaud (Cybergeo, 2015)
Many critical phenomena were described by a log periodic law (evolutionary tree, earthquake, financial index, economic crisis…). To confirm this universality we present here the appliance of a log periodic function to the succession of ski lift kinds. The agreement is good. The deceleration of this chronology from a critical epoch suggests that no new technology of lift could be expected before many years.